LOCAL SOCIO-CULTURAL KNOWLEDGE SYSTEMS AND ASSOCIATED INTANGIBLE HERITAGE PREVALENT IN UGANDAN EARTHEN ARCHITECTURE - Kenneth, Birabi Allan (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
At this time, the subject of local and as well as regional socio-cultural knowledge systems, and associated intangible heritage prevalent in African earthen architecture is seldom regarded as a worthwhile focus to warrant attention of academics, professionals and public-private sector partnerships in Africa. Yet these knowledge systems and attendant intangible heritage proliferated productive impacts towards the sustenance of indigenous education and related social-cultural values, customs and traditions of pre-Colonial African societies. Apparently, African earthen architecture provided the medium for transmission of knowledge systems together with intangible heritage. Their resilience has continued to date but at a much-reduced level of signiicance. In this connection, African earthen architecture is among the continent’s heritage fabric currently undergoing obsolescence and severe decline in enriching new generations with timeless knowledge systems. In instances of the above-noted obsolescence, the connection between intangible heritage and the African people has likewise diminished and become increasingly confused. Concomitantly, uni-dimensional globalization has taken its toll and the new generations have been left adrift. They are increasingly disconnected, and attempting to understand themselves. Consequently, their cultural landscapes and earthen-built ensembles are also threatened with disintegration. Hence, this paper highlights the compound threat to local African socio-cultural knowledge systems and associated intangible heritage prevalent in earthen architecture by means of a case study with Ugandan examples. Thereafter, the paper unfolds ‘bestpractice’ pathways for mitigating against the vulnerability of these socio-cultural knowledge systems prevalent in the earthen architecture, so as to ensure their continuity.